2016
DOI: 10.3389/fmars.2016.00023
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metagenomics of Viral Assemblages Inhabiting Four Phyla of Marine Invertebrates

Abstract: Viruses are the most abundant biological entities on Earth, killing 10-20% of oceanic biomass each day. However, despite their ecological importance, viruses inhabiting many echinoderms, cnidarians, urochordates, and marine arthropods have not been investigated with significant breadth. We conducted a broad survey of the viral assemblages inhabiting these hosts through viral metagenomics and phylogenetic analysis. Results indicate that different invertebrate groups harbor distinct viral assemblages. Interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 56 publications
3
21
0
1
Order By: Relevance
“…The concentrate was transferred to 5 Prime Phase Lock Gel and incubated with 200 ml chloroform for 10 min at room temperature. After being centrifuged for 1 min at 15,000 xg, the aqueous layer was transferred to a new microcentrifuge tube, and was treated with Invitrogen TURBO DNase (14 U), Promega RNase One (20 U) and 1 ml Benzonase Nuclease (E1014 Sigma Benzonase Nuclease) at 37 C for 3 hr (Gudenkauf and Hewson, 2016;Reyes et al, 2012). After incubation, 0.04 volumes 0.5 M EDTA was added to each sample.…”
Section: Star+methods Key Resources Tablementioning
confidence: 99%
“…The concentrate was transferred to 5 Prime Phase Lock Gel and incubated with 200 ml chloroform for 10 min at room temperature. After being centrifuged for 1 min at 15,000 xg, the aqueous layer was transferred to a new microcentrifuge tube, and was treated with Invitrogen TURBO DNase (14 U), Promega RNase One (20 U) and 1 ml Benzonase Nuclease (E1014 Sigma Benzonase Nuclease) at 37 C for 3 hr (Gudenkauf and Hewson, 2016;Reyes et al, 2012). After incubation, 0.04 volumes 0.5 M EDTA was added to each sample.…”
Section: Star+methods Key Resources Tablementioning
confidence: 99%
“…The arrival of high-throughput sequencing, however, made it possible to determine the virome of several species and different environments. Furthermore, recent metagenomic studies in invertebrates revealed distinct virome profiles both within and between host phyla [7,18]. In addition, Cornejo-Granados et al [60] found that the microbiome of P. vannamei differed significantly between wild and cultured individuals and between healthy and diseased individuals.…”
Section: Possible Causes For High Mortality In Aquaculture Settingsmentioning
confidence: 99%
“…Only a few studies have reported the metagenomic identification of novel viruses in P. monodon, in Farfantepenaeus duorarum, in copepods and in bivalves [7,[14][15][16][17]. Apart from these economically important species, few studies were published concerning the viromes of ecological important marine invertebrates, such as ghost and volcano shrimps, tunicates, non-scleractinian corals, amphipods and echinoderms [18][19][20][21][22]. However, recent comprehensive surveys have been conducted to discover the genomic diversity of multiple DNA and RNA viruses in arthropods, including marine species [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…While putative CRESS‐DNA viruses have been associated with aquatic crustaceans, including copepods (Dunlap et al., ), cladocerans (Hewson et al., ) and decapods (Gudenkauf & Hewson, ; Rosario, Schenck, Harbeitner, Lawler, & Breitbart, ), and have been linked to fluxes in invertebrate population densities (Hewson et al., ), the degree to which they alter invertebrate ecological fitness remains unclear. To date, it remains unknown if invertebrate‐associated CRESS‐DNA viruses precipitate disease or mortality in metazoans.…”
Section: Introductionmentioning
confidence: 99%